حضرت ایوب ؑ کی آزمائش قرآن کریم اور بائبل کے مابین علمی وتقابلی جائزہ: A Scholarly and Comparative Analysis of the Trial of Prophet Ayub (Job, peace be upon him) Between the Bible and the Qur'an - Aliyah Mustafa; Sana Kiran; Hafsa (International Research Journal of Arabic and Islamic Studies, 2024)
The infallibility of the Prophets (peace and blessings be upon them) is a matter of consensus among the Muslim Ummah. All Prophets are free from disbelief, polytheism, and both major and minor sins. Prophethood and Messengership are the highest ranks granted by Almighty Allah to His chosen servants. The significance of the issue of the Prophets’ infallibility can be understood from the fact that Allah has repeatedly emphasized and clarified this matter in numerous places in the Qur’an, defending the infallibility of the noble Prophets specifically. For instance, when Prophet Yusuf (Josephؑ ) was falsely accused, Allah revealed multiple verses in the Qur’an to establish his innocence and purity. On the other hand, in the Bible, various accusations and slanders have been attributed to the Prophets. Therefore, this article undertakes a comparative analysis of the personality and trials of Prophet Ayub (Jobؑ) as presented in the Qur’an and the Bible.